The Development of Curricular Guidelines for Introductory Microbiology that Focus on Understanding - Susan Merkel (American Society for Microbiology, 2012)
The number of students who leave majors in science, technology, engineering, and mathematics (STEM) due to a perception that courses are poorly taught is evidence that education reform in STEM is overdue. Despite decades of research that argues for student-centered teaching approaches, most introductory STEM courses are still taught in the large lecture format, focusing on rote memorization. While individual efforts in STEM educational reform are important, solutions will most certainly need to include institutional and cultural change. In biology, numerous national reports have called for educational reform to better prepare future scientists. We describe here a new, concept-based curriculum for Introductory Microbiology courses, designed to promote deep understanding of core concepts. Supported by the American Society for Microbiology (ASM) and based on the overarching concepts and competencies presented in the AAAS/NSF report Vision and Change in Undergraduate Biology Education: A Call to Action, we hope it will empower instructors to adapt student-centered approaches so that students in Introductory Microbiology courses can leave the course with a core set of enduring understandings of microbiology.